Change in HbA1c associated with treatment intensification among patients with type 2 diabetes and poor glycemic control. (4th May 2017) - Fu, Alex Z.; Sheehan, John J.
Abstract: Objective: We conducted a retrospective cohort study to investigate the HbA1c change associated with treatment intensification in a real-world population of patients with type 2 diabetes (T2D). Methods: Using a large US insurance claims database, patients aged ≥18 years with a T2D diagnosis and HbA1c ≥8.0% (64 mmol/mol) after ≥3 months of oral pharmacotherapy with metformin (± other oral antidiabetes agents) were identified (index date). Continuous enrollment was required for ≥12 months before (baseline) and after the index date with no baseline use of injectable antidiabetes drugs. We defined treatment intensification as prescriptions for injectable or additional oral antidiabetes drugs. Time to intensification was classified as timely (within 6 months) or not (≥6 months or not intensified). Linear regression models with propensity score 1:1 matching were performed to assess the effect of timely intensification on HbA1c. Results: Of the 11, 525 patients meeting the inclusion criteria, only 37% had treatment intensified within 6 months. Mean age at index date was 57 years, 40% of the sample was female. The mean baseline A1C was 9.4% and 9.0%, while post-index A1C was 7.9% and 8.2% for timely intensified patients versus not, respectively. Patients with timely intensification had significantly greater HbA1c reduction compared with others (−0.33%, 95% CI: −0.41% to −0.25%) within 1 year of follow up. Conclusions: In this analysis of patients with T2D and treatment failure in a real-world setting, earlier treatment intensification was associated with better glycemic control as indicated by lower HbA1c values.